Covid-19 Induced Virtual Courts Sessions in Nigeria: Practicalities and Impracticalities - Ademola Sunday-Ayeerun; Eti Best Herbert; Ngozi Chinwa Ole (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
The Presidential Declaration of Corona Virus Disease 19 as a ‘dangerous contagious disease’ occasioned the emergence of several regulations imposing restrictions on movements and social distancing measures. The Chief Justice of Nigeria and other heads of court also approved the Guidelines and Practice Directions containing modalities for virtual court sessions. This paper aims to examine the legal implications of virtual court session. The traditional requirement that court sessions should be held in places open to the public signifies a constitutional disapproval of virtual court sessions. It is contended that Practice Directions and Guidelines are weak mechanisms for entrenching virtual court sessions in Nigeria since they are within the lowest rung of the hierarchy of laws. Hence, the reform needs to be holistic. It should entail amendment of certain provisions of the constitution, laws, and rules of courts to enable a virtual innovation without legal hiccups. In alternative to constitutional amendment which usually takes long, this work, in addition to predicting the decision of the apex court on six grounds, suggests the immediate need for a judicial intervention in interpreting the constitutionality of virtual court session. This is to put to rest the fear harboured by some individuals that the serious judicial efforts put in by judges and counsel via virtual court sessions would end up becoming a nullity on appeal to the apex court.DOI: https://doi.org/10.22304/pjih.v9n2.a7